2021
DOI: 10.1111/1471-0307.12783
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus biofilm formation in Minas Frescal cheese packaging

Abstract: Despite food safety criteria for some specific foodborne pathogens that exist all over the world, the prevalence of Staphylococcus aureus in raw milk cheese is high. The biofilm formation capacity of S. aureus ATCC25923 in Minas Frescal cheese packaging at 5°C was investigated. Surface adhesion and quantification of viable adherent cells, detachment of adherent cells, biofilm viable cell count during long incubation periods and total cell count were investigated. Biofilm formation and detachment of viable cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Alonso et al observed a greater dispersion of biofilm cells in skimmed milk (Alonso and Kabuki 2019). In addition, Carvalho et al found that S. aureus has the capacity to form biofilms in low-density polyethylene packages when stored at 5 °C in the presence of Minas Frescal cheese whey, which indicates that packaging may be a potential source for dairy contamination (Carvalho et al 2021).…”
Section: S Aureus Biofilms In Food Industriesmentioning
confidence: 99%
“…Alonso et al observed a greater dispersion of biofilm cells in skimmed milk (Alonso and Kabuki 2019). In addition, Carvalho et al found that S. aureus has the capacity to form biofilms in low-density polyethylene packages when stored at 5 °C in the presence of Minas Frescal cheese whey, which indicates that packaging may be a potential source for dairy contamination (Carvalho et al 2021).…”
Section: S Aureus Biofilms In Food Industriesmentioning
confidence: 99%
“…Results from the microbiological analysis for quality of yogurt samples packed in different packaging material during 14 days of the storage period are shown in Table 3. Studies indicates that packaging may be a potential source for dairy contamination (Carvalho et al, 2021). The total amount of lactic acid bacteria in yogurt should be ranged in 106-107 CFU and yeast ≥ 102 CFU per 1 g of product (Kliks et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Staphylococcus aureus also are common foodborne pathogens and the presence of it in yogurt could be due to poor hygienic processing, handling and packaging (Prescott et al, 2004). In addition, according to (Carvalho et al, 2021) S. aureus can form biofilms in low density polyethylene packaging in Minas Frescal cheese whey, when stored at 5 °C.…”
Section: Introductionmentioning
confidence: 99%
“…MRSA infections generate higher expenses in the area of public health and leads to higher morbidity and mortality rates compared with non-resistant strains (Cosgrove et al, 2003). The prevalence of S. aureus in raw milk cheese and other different foods are high and noticed as a biofilm formation, thus, the improvements in the hygiene process are strongly recommended (Carvalho et al, 2021). Controlling the growth of both of the microbes is highly challenging for many microbiologists.…”
Section: Introductionmentioning
confidence: 99%